Nicotine patches used in combination with e-cigarettes (with and without nicotine) for smoking cessation: a pragmatic, randomised trial. Issue 1 (January 2020) - Walker, Natalie; Parag, Varsha; Verbiest, Marjolein; Laking, George; Laugesen, Murray; Bullen, Christopher
Summary: Background: Combination nicotine replacement therapy shows additive cessation benefits. We aimed to find out the effectiveness of combining nicotine patches with an e-cigarette (with and without nicotine) on six-month smoking abstinence. Methods: We did a pragmatic, three-arm, parallel-group trial in New Zealand in adult smokers who were e-cigarette naive and motivated to quit smoking. Participants were recruited from the general population using national media advertising. Participants were randomly assigned (1:4:4), with the use of stratified block randomisation, to receive 14 weeks (2 weeks before the agreed quit date) of 21 mg, 24h nicotine patches, patches plus an 18 mg/L nicotine e-cigarette, or patches plus a nicotine-free e-cigarette. We advised participants to use one patch daily, with e-cigarette use as and when necessary or desired. Participants and researchers were masked to e-liquid nicotine content. We offered 6 weeks of telephone-delivered behavioural support. The primary outcome was exhaled carbon monoxide (CO)-verified continuous smoking abstinence 6 months after the agreed quit date. Primary analysis was by intention to treat, with sensitivity analysis by per protocol, treatment adherence, varying CO cutoffs, and complete case analysis. This paper presents the main analyses and is registered with ClinicalTrials.gov, NCT02521662 . Findings: Between March 17, 2016 and Nov 30, 2017, 1124 people were assigned to nicotine patches (patches only group, n=125), patches plus a nicotine e-cigarette (patches plus nicotine e-cigarette group, n=500), or patches plus a nicotine-free e-cigarette (patches plus nicotine-free e-cigarette group, n=499). 62 (50%) of 125 participants in the patches only group withdrew or were lost to follow-up by 6 months compared with 161 (32%) of 500 in the patches plus nicotine e-cigarette group and 162 (33%) of 499 in the patches plus nicotine-free e-cigarette group. 35 (7%) participants in the patches plus nicotine e-cigarette group had CO-verified continuous abstinence at 6 months compared with 20 (4%) in the patches plus nicotine-free e-cigarette group (risk difference [RD] 2·99 [95% CI 0·17–5·81]), and three (2%) people in the patches only group (RD 4·60 [1·11–8·09]). 18 serious adverse events occurred in 16 people in the patches plus nicotine e-cigarette group compared with 27 events in 22 people in the patches plus nicotine-free e-cigarette group and four events in three people in the patches only group. In the patches plus nicotine e-cigarette group, two life-threatening serious adverse events were reported (two separate heart attacks in the one participant). In the patches plus nicotine-free e-cigarette group, one death occurred (accidental drug overdose) and one life-threatening serious adverse event (heart attack). No significant between-group differences were noted for serious adverse events, and none were treatment-related. Interpretation: Combining reduced-harm nicotine products, such as nicotine patches with a nicotine e-cigarette, can lead to a modest improvement in smoking cessation over and above that obtained from using patches plus a nicotine-free e-cigarette (or patches alone), with no indication of any serious harm in the short-term. Future e-cigarette trials should focus on their use alone or in combination with usual smoking cessation support, given issues with differential loss to follow-up and withdrawal if a usual care group is used as a comparator. Funding: Health Research Council of New Zealand.